The Social Network Ties of Group Leaders: Implications for Group Performance and Leader Reputation - Mehra, Ajay; Dixon, Andrea L.; Brass, Daniel J.; Robertson, Bruce (Organization Science, 2006)
This paper uses data from the sales division of a financial services firm to investigate how a leader's centrality in external and internal social networks is related to the objective performance of the leader's group, and to the leader's personal reputation for leadership among subordinates, peers, and supervisors. External social network ties were based on the friendship ties among all 88 of the division's sales group leaders and the 10 high-ranking supervisors to whom they reported. Internal social network ties consisted of 28 separate networks, each representing the set of friendship relations among all members of a given sales group. Objective group performance data came directly from company records. Data on each group leader's personal reputation for leadership was based on the perceptions of three different constituencies: subordinates, peers, and supervisors. Results revealed that leaders' centrality in external and internal friendship networks was related both to objective measures of group performance and to their reputation for leadership among different organizational constituencies.